Quantifying zoobenthic blue carbon storage across habitats within the Arctic’s Barents Sea - Souster, Terri A.; Barnes, David K. A.; Primicerio, Raul; Jørgensen, Lis Lindal (Frontiers in Marine Science, 2024)
Arctic sea ice extent in September (when it is at its lowest) has declined 13% per decade and the Arctic Ocean is becoming a more Atlantic influenced system. Rapid climate-forced changes are taking place in many high latitude marine ecosystems. The Barents Sea is one such high latitude Sshelf ecosystem, between about 70° and 80°N in the Norwegian Arctic. The purpose of the current study was to estimate zoobenthic blue carbon across multiple habitats within the Barents Sea (Trough, Basin, Shelf and Shallows), potentially providing values to aid ecosystem-based management of these areas under future climate change scenarios. We tested this by capture and analysis of 947 high-resolution (each 405.7 × 340.6 mm, 12 MB, 5 MegaPixel) seabed images at 17 sites with latitudinal cline, linked to collection of corresponding oceanographic data. Biotas within these images were identified to one of 14 functional groups and the density calculated.density of each of 14 functional groups. Mean stored carbon per individual was assigned by Ash MassAM (AMsh Mass) and AFDM (Ash Free Dry Mass (AFDM)) of individuals caught within Agassiz trawl deployments at the same sites. Trough sites, with the exception ofexcept for one site (B16), have low quantity of zoobenthic blue carbon compared with the Sshallows, Sshelf and Bbasin habitats. The results of a previous study that focused entirely on Trough habitats and are therefore difficult to scale up as the basis for a meaningful estimate of across-habitat zoobenthic blue carbon in the Barents Sea. Compared to the Trough and the Basin, the Sshelf and Sshallow habitats of the Barents Sea are also subjected to more trawling events through demersal fisheries and showed higher zoobenthic blue carbon stock values .